The Influence of Liquidity, Profit, Debt Policy and Operating Leverage on Price to Book Value in Manufacturing Companies listed on the Indonesian Stock Exchange - Simarmata, Lamdapot Pranata; Pasaribu, Dompak; Silitonga, Ivo Maelina; Simanjuntak, Arthur (Formosa Journal of Applied Sciences, 2024)
The research is aimed at analyzing the influence of liquidity, profits, debt policy and operating leverage on price to book value. A population of 73 manufacturing companies in the basic industrial and chemical sectors listed on the Indonesian stock exchange, 43 companies were sampled for research using purposive sampling. Research data was obtained from the site www.idx.co.id. Furthermore, the data obtained was processed using SPSS version 26. The results stated that liquidity partially had a positive but not significant effect on Price to Book Value. Profit and debt policy partially have a positive and significant effect on Price to Book Value. Operating leverage partially has a negative and insignificant effect on Price to Book Value. Liquidity, Profit, Debt Policy and Operating Leverage simultaneously have a significant effect on Price to Book Value.